2009
DOI: 10.1021/bi802356k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Peptide Amphiphile Internalization by SJSA-1 Cells in Vitro

Abstract: Self-assembly of peptide amphiphiles into nanostructures makes them attractive for a variety of applications in drug and peptide delivery. We here report on the interactions of micelles composed of a palmitoylated, pro-apoptotic peptide derived from p53 tumor suppressor protein with a human cancer cell line. Characterization of self-assembly in aqueous buffered solutions revealed formation of elongated rod-like micelles above a critical micelle concentration. Our results however demonstrate that monomers inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 60 publications
4
97
1
1
Order By: Relevance
“…This is consistent with previous results that palmitoylation of proapoptotic peptides can affect micelle stability and cell uptake. 56 The results show that there was higher osteogenic differentiation of encapsulated hMSCs when the BMP-2 peptide was dissolved in the hydrogel matrix as compared with the peptide that was conjugated (Fig. 4), which was similar to the previously reported lower activity of BMP-2 protein attached to immobilized heparin.…”
Section: Figsupporting
confidence: 89%
“…This is consistent with previous results that palmitoylation of proapoptotic peptides can affect micelle stability and cell uptake. 56 The results show that there was higher osteogenic differentiation of encapsulated hMSCs when the BMP-2 peptide was dissolved in the hydrogel matrix as compared with the peptide that was conjugated (Fig. 4), which was similar to the previously reported lower activity of BMP-2 protein attached to immobilized heparin.…”
Section: Figsupporting
confidence: 89%
“…They have been shown capable of delivering biologically active peptides for a variety of applications including angiogenesis (19,20), osteogenesis (21,22), neurogenesis (23,24), atherosclerosis treatment (25), cancer therapy (26,27), and islet transplantation (28,29). Also, peptide amphiphile micelles are comprised of a high concentration of peptide (30), inhibit peptide degradation (31), and can greatly increase peptide intracellular delivery (32). Recent research by the Tirrell Group has shown that peptide amphiphile micelles that display a tumor-specific cytotoxic T cell epitope can function as a self-adjuvanting vaccine delivery system capable of inducing a tumor-suppressing immune response when given prophylactically (33).…”
Section: Introductionmentioning
confidence: 99%
“…2 Peptide nanobres might also pierce the lipid cell membrane in the same manner as another class of brillar nanostructures, carbon nanotubes, to access the intracellular environment 3,4 due to their similarity in shape.…”
Section: Dr Krosmentioning
confidence: 99%
“…1 The non-linear glycopolypeptides presented here have the ability to spontaneously self-assemble into spherical micelles or in disk-like structures in water, a property that is not observed with their linear counterparts. 2,3 One can hypothesize that these disklike structures may bring some advantages in terms of bioactivity and we are currently developing drug delivery systems to be tested in vitro and in vivo. Professor Stupp remarked: Is there a possibility of controlling the polydispersity of the polysaccharide given that its volume fraction should affect the type of supramolecular packing observed?…”
mentioning
confidence: 99%